Justice as Recognition in the Ecological Community - Francis, Romain (University of the Witwatersrand, Johannesburg, 2022)
This thesis postulates that an alternate mode of recognition is required to develop an authentic conception of justice that reconciles the subaltern’s desire for dignity with affording greater love, care, and respect for nature. Extant redistributive and recognitive justice frames within traditional western political theory and philosophy are strictly anthropocentric and restrict nature to a purely utilitarian function in the satisfaction of human needs. This maintains a moral hierarchy between humans and nature that perpetuates ecological injustice. Using decoloniality as both a method and critical analytical framework, this thesis develops and employs the coloniality of nature to illustrate that the continued destruction, exploitation, and disrespect for nature is fundamentally tied to the misrecognition of subaltern people. Misrecognition is a product of a deep-seated sociogenic problem of coloniality introduced during European colonisation, which consolidated the superior status of a hegemonic western subjectivity. Other experiences, knowledges, practices, and ways of articulating human-nature relations were rendered as non-scientific and superstitious and devoid of any value. The misrecognition of subaltern people denied humanity an opportunity to learn from other viewpoints and integrate them into an inclusive idea of justice where no single subjectivity assumes a dominant status. Centered on a decolonial love predicated on Fanon’s idea of “building the world of the You”, not the I, Us or We, this thesis draws on the principles of transculturalism and border thinking to promulgate a practical idea of justice as recognition in the context of an ecological community, that is more inclusive of other living and non-living entities. It advances a dialogical mode of recognition that attempts to achieve the following objectives: i) promote critical introspection amongst the subaltern to understand how their experience of (mis)recognition is connected to the destruction of nature, and how their attitudes towards nature were altered by the introduction of western modernity, capitalism and colonisation, ii) enable those social groups that are on the top of the ontological hierarchy to understand their role in such processes and how to address them, and iii) to demonstrate that increasing humanity’s love, care, and respect for nature is not possible without first addressing misrecognition between people.
A thesis submitted in fulfilment of the requirements in respect of the degree Doctor of Philosophy in the Department of Political Studies, in the School of Social Sciences, in the Faculty of Humanities at the University of the Witwatersrand, in 2022.
Keywords: Recognition; Subaltern; Ecological injustice; Misrecognition; Coloniality of nature; Coloniality; Decoloniality; Transculturalism; Border thinking; Ecological community; SDG-11: Sustainable cities and communities; SDG-16: Peace, justice and strong institutions